Angioneurins: key regulators of blood-brain barrier integrity during hypoxic and ischemic brain injury - Kunze, Reiner; Marti, Hugo (Progress in neurobiology, 2019)
The loss of blood-brain barrier (BBB) integrity leading to vasogenic edema and brain swelling is a common feature of hypoxic/ischemic brain diseases such as stroke, but is also central to the etiology of other CNS disorders. In the past decades, numerous proteins, belonging to the family of angioneurins, have gained increasing attention as potential therapeutic targets for ischemic stroke, but also other CNS diseases attributed to BBB dysfunction. Angioneurins encompass mediators that affect both neuronal and vascular function. Recently, increasing evidence has been accumulated that certain angioneurins critically determine disease progression and outcome in stroke among others through multifaceted effects on the compromised BBB. Here, we will give a concise overview about the family of angioneurins. We further describe the most important cellular and molecular components that contribute to structural integrity and low permeability of the BBB under steady-state conditions. We then discuss BBB alterations in ischemic stroke, and highlight underlying cellular and molecular mechanisms. For the most prominent angioneurin family members including vascular endothelial growth factors, angiopoietins, platelet-derived growth factors and erythropoietin, we will summarize current scientific literature from experimental studies in animal models, and if available from clinical trials, on the following points: (i) spatiotemporal expression of these factors in the healthy and hypoxic/ischemic CNS, (ii) impact of loss- or gain-of-function during cerebral hypoxia/ischemia for BBB integrity and beyond, and (iii) potential underlying molecular mechanisms. Moreover, we will highlight novel therapeutic strategies based on the activation of endogenous angioneurins that might improve BBB dysfuntion during ischemic stroke.